Carbon Fiber/epoxy Interfacial Bonding Improvement by Microwave Pretreatment for Low-energy Electron Beam Curing. Issue 2 (February 2016) - Zhao, Xinming; Duan, Yugang; Li, Dichen; Zhang, Jingjing; Wang, Ben
In this paper, the prepreg of carbon fiber/epoxy (CF/EP) was pretreated by microwave radiation, and the effect of microwave radiation on the interfacial performance of the composite cured by low-energy electron beam (E-Beam) was investigated. By a rather short time microwave irradiation, the atomic ratio of O/C on the CF surface was increased, so did the oxygen-containing functional groups which helps strengthen the chemical bonding between the fiber and resin matrix. The CF surface became rougher after the microwave radiation, which would improve the bonding surface and mechanical interlocking. Compared with the untreated composite, the interlaminar shear strength (ILSS) of laminate fabricated with microwave radiated prepreg was increased by 9.6%. The SEM images showed that the resin distributed uniformly and adhered to the CF surface tightly. The interlaminar shear fracture morphology by SEM further indicated that the bonding strength between CF and EP resin was effectively improved by the microwave radiation.